Development of Lower Extremity Strength in Ambulatory Children With Bilateral Spastic Cerebral Palsy in Comparison With Typically Developing Controls Using Absolute and Normalized to Body Weight Force Values - Darras, Nicolaos; Nikaina, Eirini; Tziomaki, Magda; Gkrimas, Georgios; Papavasiliou, Antigone; Pasparakis, Dimitrios (Frontiers in Neurology, 2021)
This cross-sectional study aimed to examine the development of lower limb voluntary strength in 160 ambulatory patients with bilateral spastic Cerebral Palsy (CP) (106 diplegics / 54 quadriplegics) and 86 typically developing (TD) controls, aged 7-16 years. Hand held dynamometry was used to measure isometric strength of 7 muscle groups (hip adductors and abductors, hip extensors and flexors, knee extensors and flexors and ankle dorsiflexors); Absolute Force (AF) values in lbs were collected which were then normalized to Body Weight (NF). AF values increased with increasing age (p<0.001 for all muscle groups), whereas NF values decreased through adolescence (p<0.001 for all muscle groups except for hip abduction where p=0.022), indicating that increases in weight through adolescence leads to decreases in relative force. Both AF and NF values were significantly greater in TD subjects as compared to children with CP in all muscles and all age groups (p<0.001). Diplegics and quadriplegics demonstrated consistently lower force values than TD subjects for all muscle groups, except for the hip extensors where TD children had similar values with diplegics (p=0.726) but higher than quadriplegics (p=0.001). Diplegic patients were also exhibiting higher values than quadriplegics in all muscles, except for the knee extensors where their difference was only indicative (p=0.056). The conversion of CP subjects' force values as a percentage of the TD subjects' mean value revealed a pattern of significant muscle strength imbalance between the CP antagonist muscles, documented from the following deficit differences for the CP muscle couples: hip extensors 13% / hip flexors 32%, adductors 27% / abductors 52% and knee extensors 37% / knee flexors 53%. This pattern was evident in all age groups. Similarly, significant force deficiencies were identified in GMFCS III/IV patients as compared to TD children and GMFCS I/II patients. In this study, we demonstrated that children and adolescents with bilateral CP exhibit lower strength values in lower limb muscles as compared to their TD counterparts. This difference was more prevalent in quadriplegic patients and those with a more severe impairment. An important pattern of muscle strength imbalance between the antagonist muscles of the CP subjects was revealed.